Економічна сутність фінансової безпеки сільськогосподарських підприємств аспект - Терещенко, Максим Анатолійович; Терещенко, Максим Анатолиевич; Tereshchenko, Maksym (My University, 2017)
UK: Предметна сутність фінансової безпеки сільськогосподарських підприємств безпосередньо пов’язана з фінансовою сферою їх прояву. Вона інтегрована з категорією економічної безпеки, що є одним з найважливіших її елементів. В статті розглянуто сутність економічної категорії «фінансова безпека підприємств» та проаналізовано сучасні підходи до його трактування. Виділено складові характеристики фінансової безпеки сільськогосподарських підприємств. Запропоновано власне формулювання терміну «фінансова безпека сільськогосподарських підприємств» та його обґрунтування. RU: Предметная сущность финансовой безопасности сельскохозяйственных предприятий непосредственно связана с финансовой сферой их проявления. Она интегрирована с категорией экономической безопасности, которая является одним из важнейших ее элементов. В статье рассмотрена сущность экономической категории «финансовая безопасность предприятий» и проанализированы современные подходы к его трактовке. Выделены составляющие характеристики финансовой безопасности сельскохозяйственных предприятий. Предложена собственная формулировка термина «финансовая безопасность сельскохозяйственных предприятий» и ее обоснование. EN: Subject essence of financial safety of agricultural enterprises is directly related to the financial sphere of their display. She is integrated with the category of economic security that is one of her major elements. A financial component in the general system of economic security of agricultural enterprises is determined through strategy of realization of the resource providing of their development. Practically all component expansions of volume of menage enterprises and proceeding in composition of their assets require the increase of sum of financial resources. Choice of sources of forming of these resources, and also minimization of cost of their bringing in largely determine the level of financial independence of enterprises. Accordingly, providing of financial safety of agricultural enterprises is the inalienable constituent of financial strategy of their development.
Экономическая сущность финансовой безопасности сельскохозяйственных предприятий
Economic essence of financial safety agricultural enterprises
Keywords: сільське господарство; фінансова безпека; забезпечення фінансової безпеки; механізм; загрози; сельское хозяйство; финансовая безопасность; обеспечение финансовой безопасности; механизм; угрозы; agriculture; financial security; financial security; mechanism; threats